Analisis Kesiapan Guru dalam Menerapkan Media Pembelajaran Kurikulum Merdeka di SMPN 28 Surabaya - Hidayah, Fitri; Diantari, Shevia Dwi; Prasietyawan, Ruben Diaz (Lembaga Yasin AlSys, 2023)
Curriculum changes in Indonesia, especially the independent learning curriculum, emphasize the independence of students and the readiness of teachers in learning. The purpose of this study is to analyze the readiness of teachers at SMPN 28 Surabaya in implementing the independent curriculum teaching media. The type of research used is a qualitative approach by conducting interviews with the deputy head of the curriculum as a respondent. The data collection technique used is descriptive analytics resulting from interviews. The results show that teachers' understanding has reached an adequate level, some things need improvement, especially in providing further training to teachers who need to improve their response to curriculum changes. The role of the students involved in designing teaching media, the use of technology which is one of the helpers in using teaching media, and the obstacles encountered when designing teaching media for this independent curriculum. This conclusion is based on the empirical findings contained in the main text of this study, providing a comprehensive picture of the readiness to adopt the independent curriculum at SMPN 28 Surabaya.